Pengelolaan Sarana dan Prasarana Pendidikan di Madrasah Ibtidaiyah Tarbiyatus Syarifah Sidoarjo - Dewi, Trie Indah; Noor, Triana Rosalina (MANAZHIM, 2024)
This study aims to determine the management of educational facilities and infrastructure at MI Tarbiyatus Syarifah Sidoarjo. The research method used is a qualitative research method with data collection techniques using interview techniques with madrasa heads and vice principals in the field of infrastructure facilities, observation and documentation. The data that has been collected is analyzed descriptive-narrative. The results of this study indicate that the management of educational facilities and infrastructure at MI Tarbiyatuhs Syarifah is carried out through a process of planning, procurement, storage, inventory maintenance and deletion. In the planning process, it is carried out by coordinating with the school concerned with planning what facilities and infrastructure are needed. Regarding the procurement process, the school made adjustments to the school's needs based on the school's financial condition. For the storage process, the school carries out and utilizes a warehouse by placing the facilities that need to be stored. In the aspect of maintenance, the school carries out routine and periodic maintenance with the aim that goods are not easily damaged. For the inventory aspect, the school carries out a digital documentation process accompanied by a process of removing facilities and infrastructure for items that are no longer used or can no longer be repaired while still following the provisions applied by the school.